Mechanical and Electromagnetic Properties of Incorporating Graphene Oxide in Cementitious Mixtures - Khalil, Cherif (AUC Knowledge Fountain, 2024)
This multidisciplinary study aimed at investigating the impact of incorporating graphene oxide (GO) on the mechanical properties and electromagnetic (EM) shielding effectiveness of cementitious mixtures, as well as critically examining the mechanism with which GO affects their microstructure properties. Analysis of the literature review showed that there are discrepancies in reporting the impact of GO on the mortar mix. Consequently, this study focuses on exploring the cause for such discrepancies and identifies three main factors which are thoroughly investigated. The factors were the different sonication energies applied to the GO (Shear Mixing, 1.5 kJ/ml, 3 kJ/ml and 6 kJ/ml), the dosage of the GO incorporated in the mix (0.05%, 0.1%, 0.2%, 0.4%) as a percentage of the binder content, and the different mixing techniques (dry mixing and wet mixing) of incorporating GO in the mortar mix. Detailed analysis was conducted using Scanning Electron Microscopy (SEM), Zeta Potential, Zeta Size, Energy Dispersive X-Ray (EDX) Spectroscopy, X-Ray Diffraction Analysis (XRD), Ultraviolet-Visible (UV-vis) spectroscopy, Fourier Transform Infrared (FTIR) Spectroscopy, Surface Analysis and Porosity. These tests have all been carried out to visualize and prove the impact that these three main factors could induce to the mix. Adopting a wet mixing technique using a sonication energy of 3 kJ/ml with GO content of 0.05% of the binder content induced the optimum positive impact on the different properties tested. The compressive strength and flexural strength increased by 32% and 20.7% respectively compared to the control mix after 28 days using 0.05% GO. The results of the microstructure tests conducted (SEM, XRD, FTIR, Surface Analysis and Porosity) proved that the addition of the GO induced chemical changes/reinforcement to the cement mortar mix affecting its hydration which in turn increased its strength. Furthermore, relatively little work targeted the effect of incorporating graphene in cement mortar for shielding EM waves at low frequencies despite its promising properties. This is why this study explored the advantages of using GO in shielding EM waves at low frequencies. The frequency of interest was 2.4 GHz since Wi-Fi operates at this frequency. A comparison between the electromagnetic shielding effectiveness gains due to incorporating different dosages of GO (0.05%, 0.1%, 0.2%, 0.4%) as a percentage of the binder content used in the mortar mix have been carried out . Limited increase in EM shielding effectiveness has been identified for the 0.05% GO of only 8% (in terms of dB) relative to the control mix after 28 days. Accordingly, additional conductive material, the Iron Filling (IF), has been introduced in order to attain sufficient EM interference attenuation results, while protecting the environment. In this regard, Response Surface Methodology (RSM) using the software Design Expert v.13 was used to identify, visualize, and predict the impact of introducing three independent factors (GO, Iron Filling (IF), Silica Fume (SF)) on the compressive strength of the cement mortar mix as well as its corresponding EM shielding effectiveness. Five levels of percentage of GO (0%, 0.025%, 0.05%, 0.075% and 0.1%) of the binder content, 3 levels of percentage of IF (0%, 25%, and 50%) of the aggregate content and 3 levels of SF (0%, 5% and 10%) of the binder content were incorporated inside the software. Twenty different mix designs were produced and analyzed. The model results confirmed that increasing the GO up to 0.05% yielded the highest compressive strength results, however, additional dosage of GO had a negative impact on the compressive strength. In addition, replacing 50% of the aggregate content by IF increased the electromagnetic shielding effectiveness by 104% (in terms of dB) relative to the control mix. On the other hand, when 10% of the SF is used of the binder content, while the percentage of IF is 0% of the aggregate content and GO 0% of the binder content, the EM shielding effectiveness decreased by 7.8% (in terms of dB), however, the EM shielding effectiveness increased by 12% (in terms of dB) when the IF content became 50%, and the GO 0.1% due to incorporating 10% SF. According to the developed RSM model, the resulting cement mortar composite of 12.5 mm thickness with the highest EM shielding effectiveness provided electromagnetic attenuation up to around 11 decibels (dB) for 2 GHz frequency, and around 8 dB for 2.4 GHz frequency for the mix containing 50% Iron filling and 0.1% GO of the binder content which is deemed sufficient for the purpose of protecting structures from EM wave interference. Moreover, two empirical equations were developed from the RSM model and validated successfully for calculating the compressive strength and EM shielding effectiveness. Finally, the viability of incorporating GO in the cement mortar mix in terms of availability, transportation, and workmanship has been discussed. A cost comparison between using the proposed mortar composite section and the conventional alternative of covering the perimeter with steel sheets was presented and the results showed that it is currently practical, cost effective and environmentally friendly to shield incident EM waves using GO and iron filling. Ultimately, this study is a step on the way for researchers interested in exploring the benefits of incorporating GO to enhance the mechanical properties as well as the EM shielding effectiveness of cementitious mixtures.